Assessing accessibility to critical resources for volcanic risk management in Goma, Democratic Republic of Congo - Adalbert Muhindo Syavulisembo; François Kervyn; Moritz Lennert; Eléonore Wolff; Caroline Michellier (Volcanica)
In many administrative entities, there is little information on the accessibility of critical resources such as food, water, healthcare and fuel. Yet the lack of accessibility to critical resources can be a risk-mitigating factor. Indeed, people who are not physically threatened by a hazard can be put at risk by the fact that they lack critical resources. In the specific context of an area threatened by lava flows and characterized by a scarcity of accessible and reliable data, we assessed the accessibility of critical resources in Goma, in the Democratic Republic of Congo (DRC), a densely populated city located at the foot of the Nyiragongo volcano. Our study shows that by mapping the location of critical resources and characterizing their accessibility, we can systematically identify underserviced urban areas that are consequently more vulnerable to risks, and in our study to volcanic risks.